PENINGKATAN HASIL BELAJAR MATEMATIKA METODE FUN TEACHING PADA SISWA KELAS IV SD NEGERI 163095 - Sintaria Sintaria (PGSD Universitas Negeri Medan, 2016)
This aim of this research is to improve learning result on mathematic subject through fun teaching method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class IV, SDN 163095 Tebing Tinggi which amounted to 36 students. This study used a qualitative descriptive analysis technique. Based on data obtained from the measurement of the student learning outcomes on the cycle I of 80,55 % and cycle II amounted to 97,22 % note there is an increase in student learning outcomes. This means learning the mathematic using fun teachingmethod can improve learning outcomes in class IV SDN 163095 Tebing Tinggi.Key word :Fun Teaching, Learning Result, Mathematic